2015
DOI: 10.1017/s1930297500006987
|View full text |Cite
|
Sign up to set email alerts
|

Does telling white lies signal pro-social preferences?

Abstract: The opportunity to tell a white lie (i.e., a lie that benefits another person) generates a moral conflict between two opposite moral dictates, one pushing towards telling the truth always and the other pushing towards helping others. Here we study how people resolve this moral conflict. What does telling a white lie signal about a person’s pro-social tendencies? To answer this question, we conducted a two-stage 2x2 experiment. In the first stage, we used a Deception Game to measure aversion to telling a Pareto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 53 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…For instance, in a set of studies, participants' payoff for the number of allegedly solved tasks was either given to the participant herself (pro-self cheating), split between her and another participant (self-other cheating), or entirely given to another participant (other-only cheating) (Gino, Ayal & Ariely, 2013;Wiltermuth, 2011). Participants cheated significantly more when cheating incurred a personal benefit and was socially justifiable (i.e., self-other cheating) than when either self-profit or social justifications were present (i.e., pro-self or other-only cheating; for similar findings see also Biziou-van-Pol, Haenen, Novaro, Liberman & Capraro, 2015). The authors concluded that individuals care about both self-profit and justifications in their decision to behave dishonestly.…”
Section: Introductionmentioning
confidence: 63%
“…For instance, in a set of studies, participants' payoff for the number of allegedly solved tasks was either given to the participant herself (pro-self cheating), split between her and another participant (self-other cheating), or entirely given to another participant (other-only cheating) (Gino, Ayal & Ariely, 2013;Wiltermuth, 2011). Participants cheated significantly more when cheating incurred a personal benefit and was socially justifiable (i.e., self-other cheating) than when either self-profit or social justifications were present (i.e., pro-self or other-only cheating; for similar findings see also Biziou-van-Pol, Haenen, Novaro, Liberman & Capraro, 2015). The authors concluded that individuals care about both self-profit and justifications in their decision to behave dishonestly.…”
Section: Introductionmentioning
confidence: 63%
“…Subsequently, Erat and Gneezy (2012) observed that the sign of gender differences in lying might depend on the consequences of the lie: they found that males lie more than females in the context of Pareto white lies (lies that benefit both the liar and another person), but females lie more than males in the context of altruistic white lies (lies that benefit another person at a cost for the liar). However, the former result was not replicated by Cappelen et al (2013), who found no gender differences in the context of Pareto white lies; and the latter result was not replicated by Biziou- van-Pol et al (2015), who, in fact, found the opposite, that males tell more altruistic white lies than females. These mixed results suggest that gender differences in lying, if they exist, might be small and dependent on the consequences of lying.…”
Section: Introductionmentioning
confidence: 87%
“…Only Player 1 knows the exact allocations of money corresponding to Option A and Option B. One variant of the deception game was introduced by Biziou- van-Pol et al (2015), in order to avoid the problem of sophisticated deception (i.e., Player 1 telling the truth because he or she expects that Player 2 will not believe him or her, Sutter 2009). In this variant, Player 2 has no active choice: whether participants are paid according to Option A or Option B depends only on whether Player 1 decides to lie or to tell the truth.…”
Section: Measure Of Honestymentioning
confidence: 99%
See 2 more Smart Citations